(untitled) (Jurnal Destinasi Pariwisata, 2025)
Taman Festival Bali is an abandoned area that has the potential to be developed as a horror tourist attraction in the form of dark tourism. This study aims to identify tourism potential and develop horror narratives based on the concept of storynomics to strengthen the appeal of the area. This study uses a qualitative approach utilizing primary and secondary data. Data collection techniques include observation, semi-structured interviews with accidental sampling in informant selection, and literature studies. Data analysis was conducted using interactive data analysis techniques to support the application of Tzvetan Todorov’s narrative theory. The results show that the abandoned Taman Festival Bali has tourism potential consisting of physical potential, in the form of wild flora and fauna and abandoned buildings filled with attractive graffiti, and non-physical potential in the form of horror stories developed from local beliefs, tragic events, to tourists’ supernatural experiences. These narratives are packaged systematically using a narrative approach that includes three stages, which are equilibrium (the glory phase as an entertainment tourist attraction), disruption (the bankruptcy and abandonment phase that gives rise to horror stories), and resolution (the acceptance phase of the horror condition). This approach is in line with the principles of storynomics as a tourism promotion strategy that emphasizes the power of emotional and imaginative narratives in creating dark tourism experience.